Non-steroidal anti-inflammatory drug induces luteinized unruptured follicle syndrome in young female juvenile idiopathic arthritis patients - Tomioka, Renato B.; Ferreira, Gabriela R. V.; Aikawa, Nadia E.; Maciel, Gustavo A. R.; Serafini, Paulo C.; Sallum, Adriana M.; Campos, Lucia M. A.; Goldestein-Schainberg, Claudia; Bonfá, Eloisa; Silva, Clovis A. (Clinical rheumatology, 2018)
To assess prospectively luteinized unruptured follicle (LUF) syndrome in juvenile idiopathic arthritis (JIA) patients with and without non-steroidal anti-inflammatory drugs (NSAIDs) and healthy controls. Twenty-three adolescent and young adult female JIA patients (ILAR criteria) and 11 female healthy subjects were studied by pelvic ultrasound monitoring for follicular development and ovulation in one menstrual cycle. LUF syndrome was prospectively investigated by pelvic ultrasound with a dominant ovarian follicle without signs of follicular rupture, with elevation of serum progesterone in the luteal phase of the menstrual cycle and luteinizing hormone (LH) detected in the urine. Comparison between JIA patients with ( n = 8) vs. without NSAIDs ( n = 15) and healthy controls ( n = 11) revealed that LUF syndrome was significantly higher in the former group (2 (25%) vs. 0% vs. 0%, p = 0.049). These two patients with LUF syndrome had normal menstrual cycles without reduced ovarian reserve, and they were under naproxen 500 mg bid during the menstrual cycle. Disease duration was comparable in JIA with and without NSAIDs [19.8 (4.4–25) vs. 13 (3.1–33) years, p = 0.232]. Further comparison between JIA patients with and without NSAIDs and healthy controls showed similar mean anti-Müllerian hormone levels ( p = 0.909), estradiol ( p = 0.436), FSH ( p = 0.662), LH ( p = 0.686), and mean antral follicle count ( p = 0.240) and ovarian volume ( p = 0.363). No differences were evidenced in three groups regarding Caucasian race, body mass index, duration, and length of menstrual cycles ( p > 0.05). This is the first study to identify that JIA patients have a high frequency of LUF without impaired ovarian reserve. Future prospective studies are necessary to determine if chronic/continuous use of NSAIDs in JIA will have an impact in these patients’ fertility.